Locally-selected cacao clones for improved yield: a case study in different production systems in a long-term trial - Armengot, Laura; Picucci, Marco; Milz, Joachim; Hansen, Jon Kehlet; Schneider, Monika (Frontiers in Sustainable Food Systems, 2023)
Ageing plantations, poor genetic material, soil degradation, pests and diseases are, among other factors, limiting cacao production. To meet the increasing demand for cacao in the absence of productivity gains, forests are cleared and the use of external inputs is generalised, with severe negative impacts on biodiversity and GHG emissions. The use of improved plant genetic material should support a sustainable increase of production. In this study, we evaluate and compare the yield performance of four locally-selected clones with those of four widely-used international clones in South America and four full-sib families (crosses of the same international clones). The research was conducted in a long-term trial in Bolivia with different production systems, including monocultures and agroforestry systems under organic and conventional farming and a successional agroforestry system without external inputs. Their cacao yields and the factors determining productivity (pod index, flowering intensity, pod load, pod losses, aboveground biomass, harvesting period) were assessed during 5 years. The cacao trees grown in the two monocultures had higher yields than those in the agroforestry systems. This was the result of higher aboveground biomass, flowering intensity and pod load, and similar pod losses due to cherelle wilt and fungal diseases in the former when compared with the latter. No differences between conventional and organic management were observed. We did not identify any genotypes performing better in a specific production system. On average, the local clones had twofold and five times higher yields than the international ones and the full-sib families, respectively. This was related to their higher total pod load, bigger pods and higher yield efficiency, i.e., higher yield per unit of tree biomass. However, the local clones had less flowering intensity, more cherelle wilt and similar losses due to fungal diseases to those of the international clones. This study clearly shows the need to invest in selection and breeding programmes using locally-selected genetic material to increase cacao production and support renovation/rehabilitation plans. Breeding genetic material that is adapted to low light intensities is crucial to close the yield gap between monocultures and agroforestry systems, and to further promote the adoption of the latter.